English teachers’ knowledge for implementing the 2013 Curriculum - Sofyan A. Gani; Rina Mahjaty (English Education Journal, 2017)
The implementation of the 2013 Curriculum as a new curriculum plays an important role in the development of curricula in Indonesia. Some changes in the new curriculum require teachers to have  knowledge in spesific areas such as in the standards for content, teaching-learning processes and evaluation.  The purpose of this study was to find out the extent of the teachers’ knowledge on standards for content, standards for processes, and standards for evaluation for the 2013 curriculum. To fulfill the purpose of this study,  a sample of English teachers was taken from three State Islamic Senior High Schools in Banda Aceh. The data collected was analysed by descriptive quantitative research methods; a questionnaire was used to collect the data. The results showed that the teachers level of knowledge for implementing the 2013 Curriculum was low. This can be seen in the three standards viz: teachers’ knowledge of the standards for content, for the 2013 Curriculum was low, only 40 %; that for standards for processes  was also low, 41%, and the teachers’ knowledge about standards for evaluation was the lowest, only 36%. In order to resolve these problems, some recommendations have been made for improvement of the teacher’s knowledge of how to implement the new, 2013 Curriculum.